PERANCANGAN UI/UX PROTOTYPE MODUL PEMBAYARAN SIMRS UNIVERSITAS MATARAM DENGAN PENDEKATAN KOLABORATIF EXTREME PROGRAMMING DAN USER-CENTERED DESIGN - Husna, Nabila Ummul; Widiartha, Ida Bagus Ketut; Rosika, Herliana (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2025)
This study aims to optimize the hospital payment process at Mataram University Hospital by designing a user-friendly interface for the payment module in the HMIS. Utilizing a combined approach of XP and UCD, the research identifies opportunities to enhance user experience and streamline payment transactions. Data collection involved literature reviews, staff interviews, and observations, highlighting user needs and system limitations. The redesigned payment module is intended to facilitate structured patient transaction management while ensuring accurate financial reporting. Initial prototype testing using SUS and UEQ methods showed high usability scores, with the SUS score reaching 82 with an “excellent” grade scale and 5 out of 6 aspects of UEQ falling within the “Excellent” category range, indicating that the design was in the top 10%. The novelty aspect is in the "Good" category, indicating that 10% of other systems score better and 75% of other systems score worse. Although it did not reach “Excellent”, the system still showed an adequate level of novelty.